Observed quality of intrapartum care in Dire Dawa Administration, eastern Ethiopia - Moti Tolera Jalu; Yadeta Dessie; Tsinuel Girma; Margaret E Kruk; Bereket Yakob (International Journal for Quality in Health Care, 2026)
Abstract Background High-quality intrapartum care is essential for preventing avoidable maternal and neonatal morbidity and mortality. Although facility birth has expanded in Ethiopia, less is known about the observed content of care delivered during labour, birth and the immediate postpartum period in Dire Dawa Administration. Methods This secondary cross-sectional analysis used direct-observation and provider-survey data from a parent facility-based maternity-care study conducted in nine public health facilities in Dire Dawa Administration, Ethiopia. The facilities comprised two hospitals, five urban health centres and two rural health centres. Eligible women undergoing spontaneous vaginal birth were observed continuously from admission through childbirth and up to six hours postpartum or discharge. A total of 811 observations and data from 84 intrapartum-care providers were analysed. The observed quality of intrapartum care was measured with a structured 28-item checklist adapted from MCHiP/SMGL tools and WHO recommendations. Multilevel linear regression was used because observations were hierarchically clustered within providers and facilities. Results The mean observed intrapartum-care quality index was 48% (SD 29). Quality varied by stage of care: initial assessment 45%, first stage of labour 56%, second stage 26%, third stage 65%, immediate neonatal care 35% and early maternal postpartum care 42%. In adjusted analysis, health centres scored higher than hospitals (β = 5.50; 95% CI: 4.30 to 6.70), while rural facilities scored lower than urban facilities (β = -3.47; 95% CI: -5.49 to -1.44). Provider in-service training was positively associated with quality (β = 0.84; 95% CI: 0.34 to 1.34), whereas emergency or complication care was negatively associated with quality (β = -2.89; 95% CI: -4.42 to -1.36). Conclusion Observed intrapartum care in public facilities in Dire Dawa Administration showed substantial quality gaps, particularly during the second stage of labour and immediate newborn and early postpartum care. The findings highlight uneven adherence to recommended clinical actions across facility type, facility location and care context.